Tanggung Jawab Indonesia sebagai Negara Transit bagi Pengungsi Anak Berdasarkan Hukum Internasional - M. Riadussyah (Jurnal Hukum IUS QUIA IUSTUM, 2016)
This research examines: first, the responsibility of Indonesia as a transiting country for the child refugees based upon the international law. Second, setting the responsibility of Indonesia for the child refugees according to national law in the future. It is a normative legal research with the method of statute approach, conceptual approach, and comparative approach. The result of the research concluded that: first, Indonesia normatively has a responsibility as a transiting country though not as the party in the Convention of Refugees 1951 and protocol 1967, but bound by the convention of children rights mentioning to be responsible for giving protection to the children as the refugees. It also concluded that the custom of international law and the general law principle that is jus cogens that obliges the state to protect the human rights as a form of protection towards humanity. Second, the form of responsibility of Indonesia for the child refugees in the regulation of national law in future is that Indonesia must ratify the Convention of the Refugee 1951 with its protocol and regulate the derivative regulations of the convention.